2014
DOI: 10.18388/abp.2014_1824
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance in Rhodococcus equi.

Abstract: Rhodococcus equi is an important etiologic agent of respiratory-and non-respiratory tract infections, diseases of animals and humans. Therapy includes the use of various group of chemotherapeutic agents, however resistance acquirement is quite common. To date there is no preferred treatment protocol for infections caused by isolates resistant to macrolides and rifampicin. The resistance acquirement is a result of many molecular mechanisms, some of which include alterations in the cell envelope composition and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Antioxidants 2020, 9,114 4 of 10 redox potential of this biosensor was established recently as −290 mV [17], whereas the EroGFP2 of Mrx1-roGFP2 in response to 5 mM H2O2 was −264 mV and the intracellular redox potential during host cell infection was −260 mV. Overall, these results confirmed that rifampicin, erythromycin, and vancomycin elicited a significant oxidative stress as part of their mechanism of action.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Antioxidants 2020, 9,114 4 of 10 redox potential of this biosensor was established recently as −290 mV [17], whereas the EroGFP2 of Mrx1-roGFP2 in response to 5 mM H2O2 was −264 mV and the intracellular redox potential during host cell infection was −260 mV. Overall, these results confirmed that rifampicin, erythromycin, and vancomycin elicited a significant oxidative stress as part of their mechanism of action.…”
Section: Resultssupporting
confidence: 72%
“…Antioxidants 2020, 9,114 6 of 10 commonly used combination of erythromycin and rifampicin (Figure 3). Interestingly, norfloxacin combined with either rifampicin, erythromycin, or vancomycin had an equivalent antimicrobial effect to the antibiotherapy based on erythromycin and rifampicin (Figure 3).…”
Section: Combinatorial Antibiotherapy Against R Equi With Ros-generamentioning
confidence: 99%
See 1 more Smart Citation
“…Human patients with normal renal function should receive a loading dosage of 25–30 mg of vancomycin per kg intravenously over 1 h, followed by a regular dose every 12 h [ 26 , 27 ]. However, the practical dosing intervals can be 8, 12, 24, and 48 h based on the creatinine clearance of the patient [ 28 ].…”
Section: Therapeutic Indications Of Vancomycinmentioning
confidence: 99%
“…This facultative intracellular pathogen is transmitted by inhaling contaminated soil dust or respiratory particles produced by infected animals [6,7]. Current treatments are based on a combination of macrolides and rifampicin; however, they are becoming ineffective due to the spread of antibiotic resistance [8,9,10,11].…”
Section: Introductionmentioning
confidence: 99%